2019
DOI: 10.3389/fpsyg.2018.02526
|View full text |Cite
|
Sign up to set email alerts
|

Research on How Emotional Expressions of Emotional Labor Workers and Perception of Customer Feedbacks Affect Turnover Intentions: Emphasis on Moderating Effects of Emotional Intelligence

Abstract: Previous studies have used various external variables and parameters as well as moderator variables such as emotional intelligence have been to understand emotional labor and its related problems. However, a comprehensive model to study such variables’ correlations with each other and their overall effect on emotional labor has not yet been established. This study used a structural equation model to understand the relationship between employees’ expression of emotional labor and perception of customer feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 131 publications
(165 reference statements)
3
26
0
Order By: Relevance
“…While the role of employee empathy and deep acting has been separately examined in various service industries including call centres, hospitality (tourism/hotels/restaurants), retail, health care, education, and administrative (e.g. Grandey, 2003; Larson and Yao, 2005; Wieseke et al, 2012; Mesmer-Magnus et al, 2012; Hardy, 2017; Lee et al, 2019), no research has been found to empirically investigate how these factors together impact service quality and customer delight. In our study, we chose health care service to examine the proposed theoretical relationships as this context has the depth and variance of service experiences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the role of employee empathy and deep acting has been separately examined in various service industries including call centres, hospitality (tourism/hotels/restaurants), retail, health care, education, and administrative (e.g. Grandey, 2003; Larson and Yao, 2005; Wieseke et al, 2012; Mesmer-Magnus et al, 2012; Hardy, 2017; Lee et al, 2019), no research has been found to empirically investigate how these factors together impact service quality and customer delight. In our study, we chose health care service to examine the proposed theoretical relationships as this context has the depth and variance of service experiences.…”
Section: Methodsmentioning
confidence: 99%
“…This is a main strategy of regulating emotion that employees use to comply with expectations of emotional display (Kruml and Geddes, 2000; Hochschild, 2003). Prior research shows that employee deep acting enhances customers’ perceptions of the service experience (Grandey, 2003; Groth et al, 2009), customer feedbacks (Lee et al, 2019), and customer satisfaction and loyalty intentions (Hennig-Thurau et al, 2006; Hur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is known as surface acting. Lee et al (2019) noted that surface acting could have negative effects on employee job satisfaction, the disconnect between their true feelings and the surface acting to lead to emotional exhaustion and burnout. One instance where surface acting is necessary and almost unavoidable is where language and cultural barriers exist.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional labor was originally defined by Arlie Hochschild as the “management of feeling to create a publicly facial and bodily display” ( Hochschild, 1983 : 7). For example, service employees’ effective emotional display, contributes significantly to effective customer services ( Lee et al, 2019 ; Soderlund and Berg, 2019 ). Emotional labor is usually performed via two strategies, i.e., surface acting and deep acting ( Grandey, 2003 ).…”
Section: Introductionmentioning
confidence: 99%